Analysis of tourism planning in Tarumã (SP):: understanding its advances and obstacles (Élisée - Revista de Geografia da UEG, 2023)
This article analyzes tourism planning in the city of Tarumã (SP) in São Paulo. Since tourism is one of the fastest growing economic sectors in the world, in this geographical area, tourism is claimed as an alternative that can generate income and opportunities for local development. The methodological procedures this time consist of reading and analyzing the theoretical-conceptual bibliography, printed and electronically, which supported the empirical analysis, illuminated through on-site observations, photographic records and documental research. In favor of tourist activity in the city, there is its full potential and its varied attractions to receive tourists, as well as the political will and engagement of part of the population, among other identified advantages. Since tourism is an economic segment and a social practice, it can involve both positive and negative aspects, therefore, this study considers the fundamental role of tourism planning and its different agents involved, as a mitigation of possible obstacles to its structuring and development.
Keywords: Tourism; tourism planning; advances; barriers; Tarumã